Comparison of Synergistic Effect of Nisin and Monolaurin on the Inactivation of Three Heat Resistant Spores Studied by Design of Experiments in Milk - Souhir Kmiha; Chedia Aouadhi; Khouloud Aziza; Awatef Bejaoui; Abderrazak Maaroufi (Journal of Food Quality)
Spore forming bacteria are special problems for the dairy industry. Heat treatments are insufficient to kill the spores. This is a continuously increasing problem for the industry, but we should be able to control it. In this context, we investigated the combined effect of nisin, monolaurin, and pH values on three heat resistant spores in UHT milk and distilled water and to select an optimal combination for the maximum spore inactivation. The inhibitory effect of nisin (between 50 and 200 IU/ml), monolaurin (ranging from 150 to 300 µg/ml), and pH (between 5 and 8) was investigated using a central composite plan. Results were analyzed using the response surface methodology (RSM). The obtained data showed that the inactivation of Bacillus spores by the combined effect of nisin-monolaurin varies with spore species, acidity, and nature of the medium in which the bacterial spores are suspended. In fact, Terribacillus aidingensis spores were more resistant, to this treatment, than Paenibacillus sp. and Bacillus sporothermodurans ones. The optimum process parameters for a maximum reduction of bacterial spores (∼3log) were obtained at a concentration of nisin >150 IU/ml and of monolaurin >200 µg/ml. The current study highlighted the presence of a synergistic effect between nisin and monolaurin against heat bacterial spores. So, such treatment could be applied by the dairy industry to decontaminate UHT milk and other dairy products from bacterial spores.